2015
DOI: 10.1002/rmv.1823
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in HPV‐associated cancers and therapeutic implications

Abstract: Human papillomaviruses (HPVs) are small double-stranded circular DNA viruses with 8 kb genomes. So far, more than 150 HPVs have been identified, and 12 types of HPVs have been conclusively linked to cancer by the International Agency for Research on Cancer/World Health Organization. Expression of HPV E5, E6 and E7 oncoproteins can alter multiple signaling pathways to cause cancer. In this review, the signaling pathways activated by these oncoproteins are summarized, and targeted therapy against key signaling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 333 publications
(396 reference statements)
2
71
0
1
Order By: Relevance
“…Conversely, exogenous HPA can activate this process [21]. HPV E6 and E7 proteins, two main carcinogenic proteins, can cause cellular transformation via their actions on multiple signal transduction pathways [22]. By increasing p53 ubiquitination, HPV E6 reduces the ability of p53 to activate the promotor of HPA, leading to a higher HPA expression [23, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, exogenous HPA can activate this process [21]. HPV E6 and E7 proteins, two main carcinogenic proteins, can cause cellular transformation via their actions on multiple signal transduction pathways [22]. By increasing p53 ubiquitination, HPV E6 reduces the ability of p53 to activate the promotor of HPA, leading to a higher HPA expression [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…By increasing p53 ubiquitination, HPV E6 reduces the ability of p53 to activate the promotor of HPA, leading to a higher HPA expression [23, 24]. E6 stabilizes h-TERT mRNA and increases h-TERT expression, thus leading to an increase in telomerase activity [22]. Tang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The specific activities of E5, E6, and E7 have been recently reviewed by Chen and colleagues. [58] Recent data in cervical cancer cells lines have demonstrated that activation of the PI3K pathway induces the ubiquitination of PTEN leading to compounded, uncontrolled positive feedback [59]. Given these mechanistic studies pointing to acquired PI3K pathway activation, investigators tested downstream mTOR inhibition and found potent in vivo activity utilizing cell line derived xenografts [60].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Expression of HPV E5, E6, and E7 oncoproteins can alter multiple signaling pathways to cause cancer. 118 Unfortunately, infection with high-risk HPV, such as 16 and 18, plays a major role in the incidence of cervical cancer. …”
Section: Other Type Of Cancersmentioning
confidence: 99%